The Influence of the Tam Dimension on Intention to Reuse the Bukalapak Application: Customer Satisfaction as a Mediating Variable - Satya Weda Witawan; Putu Yudi Setiawan (Borong Newinera Publisher, 2024)
The purpose of this study is to examine how customer satisfaction mediates the relationship between perceived convenience and usefulness and reuse intention. The investigation was conducted in Bali's Denpasar City. The population of Denpasar City Bukalapak users under investigation is indeterminate, meaning that its exact number cannot be determined. The purposive sampling method, or the process of choosing the sample while taking specific factors into account, is the approach utilized in sample selection. The inferential statistics employed in this study are partial least square (PLS)-based structural equation modeling (SEM) analysis. Perceived convenience and usefulness have a positive and significant influence on customer satisfaction, which in turn has a positive and significant effect on customer satisfaction, which in turn has a positive and significant effect on intention to reuse, and which partially mediates the influence of perceived usefulness, according to the research findings. and purpose to reuse perceived simplicity of use. Based on the research findings, it can be said that intentions to reuse are higher when perceived utility and convenience are higher. Therefore, client satisfaction increases with perceived utility and convenience. Increased customer satisfaction correlates with higher intention to reuse. Customer happiness rises with perceived usefulness and convenience, which in turn leads to an increase in the desire to reuse. Bukalapak's suggestions include enhancing customer service abilities, offering distinct phases of use till the transaction is completed, and including features that are utilized for its consumers' transaction demands.